1999
DOI: 10.1093/bja/83.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a remifentanil bolus dose on the cardiovascular response to emergence from anaesthesia and tracheal extubation

Abstract: We have examined the effect of remifentanil on the haemodynamic response to emergence from anaesthesia and tracheal extubation in 40 ASA I-II female patients undergoing diagnostic laparoscopy, in a randomized, double-blind study. All patients received a standard general anaesthetic comprising propofol, vecuronium and 1% isoflurane with 66% nitrous oxide in oxygen. At the end of surgery, a bolus dose of remifentanil 1 microgram kg-1 (n = 20) or saline placebo (n = 20) was given and tracheal extubation was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 5 publications
0
46
0
Order By: Relevance
“…3,4 Many studies have investigated strategies to attenuate hyperdynamic responses, including extubation under deep anaesthesia and the use of calcium-channel blockers, b-blockers or short-acting opioids. [5][6][7] However, although extubation during the deep planes of anaesthesia avoids cardiovascular stimulation, it can also depress the respiratory and circulatory systems and occasionally results in difficulty managing the upper airway; 5 drug treatments have not been fully successful. 6,7 Dexmedetomidine is a highly specific a2-agonist with sedative, analgesic and sympatholytic effects without significant respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many studies have investigated strategies to attenuate hyperdynamic responses, including extubation under deep anaesthesia and the use of calcium-channel blockers, b-blockers or short-acting opioids. [5][6][7] However, although extubation during the deep planes of anaesthesia avoids cardiovascular stimulation, it can also depress the respiratory and circulatory systems and occasionally results in difficulty managing the upper airway; 5 drug treatments have not been fully successful. 6,7 Dexmedetomidine is a highly specific a2-agonist with sedative, analgesic and sympatholytic effects without significant respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent a high dynamic response and choking in the recovery process of general anesthesia and extubation, many methods, such as deep anesthesia extubation, the use of local anesthetics, vasodilators, short-acting opioid drugs, and other methods, have been used in the clinic (Shajar et al, 1999;Hohlrieder et al, 2007). Studies have reported that the application of general anesthesia with propofol or remifentanil could make the recovery process of patients smoother (Shajar et al, 1999;Wilhelm et al, 2001;Blayney et al, 2003;Hohlrieder et al, 2007). However, propofol and remifentanil, which are more conducive to allowing patients to pass through the recovery period safely, have been less characterized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in clinical anesthesia (Hughes et al, 1992;Kapila et al, 1995;Soltesz et al, 2001). Recent studies have shown that the use of remifentanil can benefit patients who are awake (Shajar et al, 1999;Wilhelm et al, 2001;Hohlrieder et al, 2007). The purpose of this study was to investigate the effect of maintaining an intravenous infusion of remifentanil or propofol on the performance of general anesthesia, including the cardiovascular response, choking, and irritability at the end of general anesthesia, in order to assess the effect of a maintenance intravenous infusion of remifentanil or propofol.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Both of these drugs can suppress the cardiovascular response during emergence. 20,21 A continuous infusion of remifentanil between 0.05 to 0.075 µg·kg -1 ·min -1 has been demonstrated to provide good intubating conditions. 18,19 When remifentanil was used alone, a high incidence of recall was reported.…”
Section: Discussionmentioning
confidence: 99%